In vivo client proteins of the chaperonin GroEL-GroES provide insight into the role of chaperones in protein evolution - Taguchi, Hideki; Koike-Takeshita, Ayumi (Frontiers in Molecular Biosciences, 2023)
Protein folding is often hampered by intermolecular protein aggregation, which can be prevented by a variety of chaperones in the cell. Bacterial chaperonin GroEL is a ring-shaped chaperone that forms complexes with its cochaperonin GroES, creating central cavities to accommodate client proteins (also referred as substrate proteins) for folding. GroEL and GroES (GroE) are the only indispensable chaperones for bacterial viability, except for some species of Mollicutes such as Ureaplasma. An important goal in GroEL biology is to identify a subset of obligate GroEL/GroES clients to elucidate the roles of chaperonins in the cell. Recent advances revealed hundreds of in vivo GroE interactors and obligate chaperonin-dependent clients. This review summarizes the progress on the in vivo GroE client repertoire and its features, mainly for Escherichia coli GroE. Finally, we discuss the implications of the GroE clients for the chaperone-mediated buffering of protein folding and their influences on protein evolution.